Effects of First Aid Diabetes Mellitus Program using the Creative Drama Process for Village Health Volunteers - Vichaipon, Chanthawan; Vichaipon, Seksan; Chaisongmuang, Penpuk; Kumpiriyapong, Nattanun; Chondaeng, Kongkrissadakorn (Nursing Journal of The Ministry of Public Health, 2025)
The potential of village health volunteers has a direct impact on supporting public health care. This quasi-experimental research aimed to examine the effects of the first aid diabetes mellitus program using the creative drama process on knowledge, skills, and self-confidence in village health volunteers. The sample consisted of 42 village health volunteers who were selected by simple random sampling technique. The experimental group (n=21) received the first aid program for diabetic patients using the creative drama process for 5 weeks, which consisted of 4 steps: physical and mental preparation, motivation, preparation of drama skills and drama activities, and evaluation. The contents of this program included first aid training for looking after diabetic patients suffering with hypo-hyperglycemia, drowsiness, seizures, shock, and unconsciousness. The comparison group (n=21) received a first aid diabetes mellitus program according to the standards of the sub-district health promoting hospital. The research instruments included the knowledge- related first aid for patients with diabetes mellitus questionnaire, skill assessment scale, and self-confidence appraisal scale. Their content validities were checked, and the reliability coefficients were found to be .79, .77, and .95, respectively. Data were analyzed using paired t-tests and independent t-tests. The results demonstrated that the mean scores of knowledge related to first aid for patients with diabetes mellitus, skills, and self-confidence in the experimental group were higher than before providing the program and were significantly higher than the comparison group. Therefore, the first aid program for diabetic patients using the creative drama process can be able to increase knowledge, skills, and self-confidence in village health volunteers to provide first aid for diabetic patients with emergency complications before transferring them to the medical facility.